Growth without development: The post-WWI period in the Lower Danube : perspectives and problems of Romania and Bulgaria - Alberto Basciani (The Journal of European Economic History, 2020)
This article examines the reaction of the Romanian and Bulgarian ruling classes to the great transformations in South-East Europe in the aftermath of World War I. The conflict had revealed the intrinsic weakness of the economic and social structures of all the Balkan nation-states, victors and vanquished alike. This awareness prompted politicians in Romania and Bulgaria to seek massive industrialization accompanied by some social reforms (agrarian reform, education, etc.) with a view to decisive modernization. A strong industrial base supported by the state through protective policies and public orders seemed the fastest and safest way to transform the economic structure of the two countries, which until then had been predominantly agrarian. This economic action was accompanied by a lively scientific and cultural debate fueled by Bulgarian and Romanian economists convinced that industrialization was the only way to achieve emancipation from underdevelopment and subjection to the Western powers. On the whole, however, this policy approach, artificially supported by the state and inadequately powered by a modest internal market, did not prove capable of reversing the trend of Bulgarian and Romanian development. On the contrary, it had the effect of shifting precious resources away from the countryside, which remained mired in severe technical and human underdevelopment.
Keywords: 330